(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2013)
This study investigates the motives behind the adoption of Hangeul, the Korean alphabet, by the Cia-Cia ethnic group in Baubau, Sulawesi, Indonesia. The import of Hangeul exemplifies how Indonesian peripheries have tried to form their own regions as distinctive entities against the nation. Their attempts to do so expand beyond the nation in hopes of emerging as new centres in a decentralised Indonesia, in which new power dynamics can be negotiated. Furthermore, this case portrays how the local population copes with growing ethnic identities and the mission of modernisation simultaneously.